Recommendations from the Sociedade Portuguesa de Cuidados Intensivos and Infection & Sepsis Group for intensive care approach to COVID-19 - Mendes, João João (Rev Bras Ter Intensiva, 2020)
Current COVID-19 epidemics was declared on December 31, 2019 at the Wuhan city seafood market, rapidly spreading throughout China, and later reaching several countries (mainly South Korea, Japan, Italy and Iran) and, since March 1, reaching Portugal. Most of the infected patients present with mild symptoms, not requiring hospitalization. Among those admitted to the hospital, 6% to 10% require admission to the intensive care unit. These recommendations are aimed to support the organization of intensive care services to respond COVID-19, providing optimized care to the patient and protection for healthcare professionals.